Studying the effect of common intestinal parasites on the digestive system of children - Muntasir Nizar Mahmoud Hazaa; Athmar Zedan Youssef Hudhod; Hadeel Ward Hamid Shanawa; Karar lazim Marihej Haider; Mortada Nizar Hameed Habtar (Genius Journals, 2024)
The results of the current study, according to scientific research, showed that approximately 20% of children are infected with intestinal parasites, and that the age group (4-5) years has the highest infection rate.
Keywords: children; group; intestinal parasite